Perception of integrative care in paediatric oncology-perspectives of parents and patients - Wiebke Stritter; Britta Rutert; Christine Eidenschink; Angelika Eggert; Alfred Längler; Christine Holmberg; Georg Seifert (Elsevier, 2021)
Purpose: For some years now, a programme for the use of integrative care in paediatric oncology has been established in a German university hospital and offers patients and parents complementary treatment options. According to their medical condition and wishes. A variety of external applications such as medical wraps, warm oil compresses and rhythmic embrocations are offered. This article analyses how patients and parents perceived and experienced the integrative care program. Methods: In this qualitative study, data consists of field notes conducted through participant observation, informal conversations and interviews with parents (n = 25) during the implementation phase of the program. Data was analysed on basis of thematic analysis and organized with the analysis software MAXQDA. Results: Parents and families intuitively developed strategies for dealing with crisis situations such as childhood cancer. In addition, many of the families brought with them a wealth of experience in complementary medicine. Parents perceived the integrative care treatments as soothing, relaxing and pain-relieving for their child. Patients could relax and side effects of chemotherapy were alleviated. However, children, who undergoing chemotherapy were not always open for physical touch and thus sometimes also rejected the treatments sometimes. Conclusion: The analysed integrative care programme is perceived as a strong patient and family-centred approach of support during the oncological paediatric treatment. From a salutogenetic viewpoint, this program aims to strengthen the dimension of manageability within the concept of sense of coherence. Parents are given supportive means to manage side effects and ease their child's suffering, through touch and attention that can be very beneficial.